Therapeutic Applications of Novel Drug Delivery Systems of Liquorice: An Updated Review on Recent Advancements: Drug Delivery Systems of Liquorice - Sanshita; Taneja, Ayushi; Sangnim, Tanikan; Huanbutta, Kampanart; Sindhu, Rakesh K; Singh, Inderbir (Scripta Medica, 2024)
In recent times, individuals are focusing more on natural substances, primarily due to their safety and non-toxicity. Also, there is an increasing demand by industries for the phytoconstituents that might be incorporated in pharmaceuticals, cosmetics, dietary products and nutraceuticals. Liquorice is one of the widely used Chinese herb since ancient times due to its medicinal properties. It exhibits broad spectrum biological activities such as anti-inflammatory, immunomodulatory, anti-oxidant, anti-cancer, anti-diabetic, anti-microbial properties, and is used in the treatment of different diseases such as cancer, inflammation, viral infections, cardiovascular and respiratory disorders. Different novel formulations such as nanoparticles, microparticles, liposomes, nanomicells and self-emulsifying drug delivery system are developed that overcome major limitations of liquorice including its low solubility, stability and less bioavailability. In this review, we discuss about liquorice, its historical background, pharmacokinetics, therapeutic applications, its different mechanism of actions, with major emphasis on liquorice encapsulated novel formulations (nanoparticles, nanomicelles, liposomes, niosomes, microparticles, microspheres, self-nanoemulsifying system, self-micro-emulsifying system). Also included brief description of pre-clinical studies and liquorice containing marketed products. Liquorice, a prominent constituent of different dietary products, has aroused the interestof many researchers because of its anti-proliferative capacity, tumour microenvironment manipulation and autophagy activation in numerous cancer types. Nanotechnology-based techniques for enhanced solubilization, stability and targeted drug delivery have been tested by formulation scientists. Liquorice is enclosed in different novel carriers and encapsulated liquorice displayed enhanced stability, solubility, high encapsulation efficiency, controlled drug release,and extended circulation time period.
Keywords: Glycyrrhiza; Liquorice; Applications; Nanoparticles; Liposomes